Technological innovations in the outside-hospital emergency service: a literature’s review (Dissertation Nursing, 2025)
BACKGROUND: The use of advanced technologies significantly improves the timeliness and quality of healthcare, especially in out-of-hospital emergency settings. Digital Health promotes a person-centered healthcare system and technological innovation. Objective: This narrative review aims to identify new technologies applicable to the out-of-hospital urgent and emergency system, with particular attention to the Health Alarm System. It also seeks to evaluate the impact of these technologies on the quality of telephone dispatch and the effectiveness of rescue interventions.METHODS: The research was conducted in July 2023 using databases PubMed, Cinahl-Ebsco, Ilisi, Google Scholar, and Cochrane Library. Studies published since 2013 in English or Italian, available in full-text format, were included.RESULTS: Innovative technologies improve the management of out-of-hospital emergencies. Among the main findings, three articles address continuous patient monitoring, four discuss the rapid transmission of geolocation data and clinical conditions via SMS and email, and four focus on the use of video calls, which enable dispatchers to visually assess and provide real-time support.CONCLUSIONS: The adoption of technology in out-of-hospital emergency services enhances dispatcher-caller interaction, performance quality, and response times. However, many technologies are still experimental or underused, resulting in fragmented application.
Keywords: Digital Health; Emergency; Videocall; Health Alarm System